(untitled) (International Journal of Occupational Safety and Health, 2026)
Introduction: The automotive industry in Malaysia has a high rate of workplace accidents, highlighting concerns about the effectiveness of safety culture. Safety culture reflects workers’ attitudes and behaviors toward safety and can influence accident outcomes. Therefore, this study aims to assess the safety culture maturity level and its associated sociodemographic and occupational factors among automotive workers in Malaysia. Methods: This cross-sectional study was conducted at one of the largest automotive factories in Malaysia. Survey data were collected for over one month, from early August to September 2022, from 387 workers in the manufacturing division using a non-probability sampling method. A standardized 28-item SASTO questionnaire was administered. Results: Most respondents were between eighteen and thirty years old (32.3%), male (63.3%), with an education level of Sijil Pelajaran Malaysia (49.1%), working as operators (76.0%), with one to ten years of work tenure (52.7%), and no history of occupational accidents (79.3%). The results indicated that the average level of safety culture maturity among the respondents was 3.46 (SD = 0.94), indicating a proactive stage. Among the aspects of safety culture, the organizational aspect had the highest mean level (M = 3.48, SD = 1.05), followed by the psychological aspect (M = 3.46, SD = 0.82), and the behavioral aspect (M = 3.42, SD = 0.98)In multivariate analysis, significant associations were found between gender (β = 0.145), educational level (β = 0.156), had history of occupational accidents (β = 0.346), and departments (β = 0.171) with the level of safety culture maturity. The most dominant factor was the history of occupational accidents. Conclusion: The safety culture among workers exhibits a generally positive level, even with areas identified for potential improvement. This safety culture is influenced by their sociodemographic and working backgrounds, as well as their history of occupational accidents. Therefore, it is recommended that future intervention strategies for preventing occupational accidents consider these factors to ensure their effectiveness.